Dietary factors influencing the COVID-19 epidemic process - S. V. Ponomarenko (Фармакоэкономика)
Objective: to analyze the role of diet in the epidemiological parameters of the SARS-CoV-2 Coronavirus and identify factors that correlate withthe reduction in the severity of the consequences of COVID-19 disease, namely the rate of prevalence (RPr) and infection fatality rate (IFR) in different regions.Material and methods. The information and data required for this study were found in scientific publications and the media available on the Internet, as well as obtained from statistical databases using specific keywords, both for a single tag and in various combinations of them. Statistical samples were managed from sources and facts available on the Internet. Pearson correlation coefficient (r) was used to understand a statistical relationship between two variables.Results. The relationship between nutritional factors and the impact of the 15-month COVID-19 pandemic in different regions was investigated using various available statistics for five continents and 47 countries. A clear relationship was found between the outcomes of the SARSCoV-2 epidemic (RPr and IFR) and the amount of consumed essential nutrients, with correlations in the negative range r=–0.98 and r=–0.66 for plant proteins and with correlation coefficients r=0.92 for animal proteins. Also, excessive sugar consumption increased the severity of COVID-19 with correlation coefficients in the range of r=0.99–0.72 in the representative samples.Conclusion. Statistical analysis presented that the number of diagnosed patients with SARS-CoV-2 (RPr) and deaths from COVID-19 (IFR) was significantly lower in regions where more plant foods were consumed than animal products. A detailed study of the relationship between the Coronavirus and the host as well as the metabolism of protein and sugar may reveal the diet factors responsible for resistance to the pathogen. Edible plants can contain components responsible for suppressing the replication cycle of the SARS-CoV-2 virus. Biochemical investigation of these components would help in the development of etiological oral administrated anti-COVID-9 medicine.